Factors influencing paddy farmers’ attitude and intention to adopt organic paddy farming in the Central Java Province, Indonesia - Ashari, . (2019)
In Indonesia, organic rice production was the norm prior to the implementation of the green revolution (GR) technology. GR technology, which drove massive use of agrochemicals resulted in highly dependent farmers, has threatened much of the environment and human health. The back to nature lifestyle, creating much awareness of the negative impacts of agrochemical inputs, has stimulated increase in demand for organic rice triggered by the country’s initiatives. With enormous resources, organic paddy farming holds good prospect. However, the rate of adoption to the new planting scheme has been low. There exist problems between tendency and actual adoption. The underlying factors influencing farmers’ decision to adopt become imperative and needed to be investigated. Theoretically, actual behavior to adopt change may be gauged by intention. Knowing the factors influencing intention is essential to understand farmers’ behavior in adoption. Hence, the objectives of the present study were to examine the distinct nature of farmers’ perception, in terms of attitude and behavioral intention toward technology; to investigate the relationships between farmers’ socio-economic and attitude/intention; and to analyze factors influencing same toward organic farming. In addressing the issues, two basic theories, namely The Theory Planned Behavior (TPB) and Theory Acceptance Behavior (TAM), were used. Conducted in Sragen District, Central Java Province, the study applied a multi-stage sampling method. A total of 600 respondents, comprising of 300 semi-organic and 300 conventional paddy farmers from five sub-districts, were selected. The study utilized nine constructs, i.e., perceived usefulness (PU), perceived ease of use (PEU), attitude (AT), environmental concern (EN), perceived behavioral control (PBC), subjective norm (SN), perceived risk (PR), moral obligation (MO) and behavioral intention (BI). All constructs, represented by measurement variables, used Likert-Scale which ranged from 1 (strongly disagree) to 7 (strongly agree). Data were analyzed by both descriptive and inferential statistical analyses using Structural Equation Model (SEM). The study revealed that all participating paddy farmers had positive perception toward organic farming. Among semi-organic farmers, socioeconomic variables, i.e., age, education, and non-agriculture income had significant relationships with attitude (AT). Factors that strongly influenced attitude were PU, PEU, and EN. The study also showed that determinants for behavioral intention (BI) were AT, SN, PBC, and MO. PEU and AT were two strongest determinants for attitude and intention, respectively. Among conventional farmers, levels of education and experience, and sources of income were found to be significant. Participation in integrated pest management, education, and non-agriculture income yielded significant relationships with intention. The determinant factors for attitude were PU and EN while the determinants factors for behavioral intention were AT, SN, PBC, MO and PR. The strongest determinants for attitude and intention were PU and SN respectively. As new construct to the model, EN had significant contribution to both groups of farmers. The significance of EN and MO on attitude and intention implies that the adoption of organic farming system should also consider aspects of morality and environmental consciousness. The study suggests that in order to increase adoption rate, for semiorganic paddy farmers must consider establishing positive attitude toward organic farming, while conventional farmers must secure the involvement of influential people to encourage farmers’ adoption.